Correlating Light and Thermal Stability of Silver Carboxylate Complexes by Infrared and 13c Nmr Spectroscopy - Paez-Collio, M; Paez-Collio, M; Guerrero-Nunez, J; Guerrero-Nunez, J; Azocar-Guzman, M; Azocar-Guzman, M; Tamayo-Villarroel, L; Tamayo-Villarroel, L; Levín-Vásquez, P; Levín-Vásquez, P (Taylor and Francis Ltd., 2016)
Bond nature of carboxylic groups can play an important role in Ag(I)-carboxylate compounds because light and thermal stability are important requirements for future applications such as antibacterial additives. A linear correlation between bond character and light stability of silver carboxylate complexes has been predicted by a direct relationship of infrared and 13C NMR spectroscopic data. This correlation is in agreement with the thermogravimetric analysis and provides a new approach to explore the interaction and the physical properties of metal-carboxylate bonds. © 2016 Informa UK Limited, trading as Taylor & Francis Group.